A revised approach to trend employment projections in long-term scenarios - Cavalleri, Maria Chiara (OECD Publishing, 2017)
The paper describes revisions to the trend employment component of the production function underpinning long-term economic scenarios. Starting with historical age and sex-specific employment rates, a novel approach is developed to correct for cyclical effects using the country-level employment gap while allowing the different sex and age groups to exhibit different sensitivities to the economic cycle. From the resulting cyclically adjusted age/sex-specific employment rates, trend entry and exit rates into/out of employment are computed using the traditional cohort approach. The different employment propensities of existing cohorts are then used to project future employment rates, with entry and exit rates of new cohorts assumed to mimic the most recent ones. To construct scenarios, the model allows a number of policy settings to influence employment rate projections, notably the legal retirement age, tax wedges, family benefits, etc. The sizes of these effects are sourced from recent OECD work on the quantification of structural reforms, and are also specific to sex and age groups. The trend total employment projection is obtained by aggregating age/sex-specific employment rate projections using external demographic projections
Keywords: Employment; Economics